TEKNIK SINEMATOGRAFI PADA DOKUMENTER “LENGGAK NGAYUN SI TANDUK BAJA” SEBAGAI KAMPANYE PELESTARIAN SENI BUDAYA GARUT - Kutanto, Haronas; Ibrahim, Aditiya (Universitas Budi Luhur, 2023)
Agility art contest tradition of sheep Garut is the hereditary tradition that used to be known as the tradition of Buffalo sheep, where both the lamb must still compete until one of them dead to find who the winner. However, over time, farmers began to realize that different arrowroot sheep with lamb in General, they continued to do various kinds of changes until in the end the tradition of Buffalo sheep is now transformed into a tradition of art contest Garut sheep agility. Changes made to them including sheep should get special treatment before competition, the setting of the game, and conduct the assessment is determined based on the elements of the art of accompaniment music Nayaga. Change is what keeps society campaigned arrowroot to eliminate a negative view of the associated existence of gambling in every game. Because it is considered that for gambling is actually a process of bargaining between the prospective buyer with a cattlemen, where the selling price of the sheep who won the contest will soar up to hundreds of millions of dollars. So, often a number of breeders utilize this contest as a sheep marketing area is also becoming a new way to boost their economies. Preservation of tradition is becoming a reference for creators to formulate the idea of creation of the work of the documentary portrait of a culture in order to help the community in Garut who were campagned the tradition of their ancestors. In the making of this movie, the creators used a technique that includes cinematography, camera angles, continuity, cutting, close-ups and composition to maximize the message of the story through the pictures shown. Through this film, the creators expect the general public can better understand what kind of tradition art contest agility sheep Garut has changed and there is no gambling in it.